The new genus Acrocephalomyia, and a new species of Ropalomera from Costa Rica, with additional records for other Mesoamerican species (Diptera: Ropalomeridae) - Ibáñez-Bernal, Sergio; Hernández-Ortiz, Vicente (Zootaxa, 2012)
New taxa of the family Ropalomeridae from Costa Rica are described, and additional records of ropalomerid flies fromMexico and Central America are provided. The new genus and species Acrocephalomyia zumbadoi can be easily distin-guished from all other ropalomerid genera by the following combination of characters: angular forward projection of head,absence of ocelli, flat face, bare arista, long scutum, and scutellum triangular-shaped and dorsally flattened with only onepair of apical bristles with bases approximated. The new species Ropalomera aterrima can be recognized from congenersby remarkable differences of the head, the shape of the scutellum, the absence of scutal vittae, fumose wings, and by theblack coloration of the body, ocellar bristles large, one postpronotal bristle, scutum without pollinose vittae and flat scutellum. Lenkokroeberia chryserea Prado and Kroeberia fuliginosa Lindner are newly confirmed for Costa Rica.